Modeling the Influence of Social Media-Based Educational Marketing on Prospective Students' Enrollment Intentions - Basri; Ilham; Widyatmike Gede Mulawarman; Nurlaili (Journal of Pedagogy and Education Science, 2026)
This study aims to analyze the effectiveness of social media-based educational marketing strategies in increasing prospective students’ interest in madrasahs in Samarinda City by considering the roles of content quality, usage intensity, and engagement, as well as institutional image as a mediating variable. This research employs a quantitative approach with an explanatory design and is analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The sample consists of 150 respondents, including prospective students and parents who have accessed madrasah social media. The results indicate that content quality (β = 0.32; t = 4.85), usage intensity (β = 0.28; t = 3.92), and engagement (β = 0.35; t = 5.10) have positive and significant effects on institutional image, with engagement being the most dominant factor. Furthermore, content quality (β = 0.21; t = 2.98), usage intensity (β = 0.18; t = 2.45), and engagement (β = 0.22; t = 3.10) also significantly influence prospective students’ interest. Institutional image has the strongest effect on interest (β = 0.41; t = 6.25). The R² values of 0.68 for institutional image and 0.72 for interest indicate strong explanatory power of the model. In addition, institutional image is proven to act as a partial mediator in the relationship between social media marketing strategies and prospective students’ interest. This study concludes that the effectiveness of social media-based educational marketing is strongly determined by content quality, consistency of use, and audience engagement in building a positive institutional image. The findings highlight the importance of interactive and integrated digital strategies to enhance the attractiveness of madrasahs in the digital era.